A general model for predicting aeolian transport rate over sand surfaces with vegetation cover. Issue 10 (10th May 2022) - Li, Huiru; Liu, Chenchen; Cheng, Hong; Zou, Xueyong; Zhang, Chunlai; Liu, Bo; Li, Jifeng; Kang, Liqiang; Wu, Yongqiu
Abstract: Aeolian sand transport is caused by wind erosion, which is the main cause of environmental problems such as land desertification, blown sand disasters and air pollution. Previous research results and engineering practices have confirmed that vegetation improvement has long‐term and comprehensive benefits for controlling aeolian sand transport. The role of vegetation in aeolian sand transport can be explained by the complexity of atmospheric, earth and biosphere systems. However, the lack of a universal model used to predict aeolian transport rate on vegetated surface results in different understandings about vegetation effects due to different experimental methods and materials. To clarify the effect of vegetation on aeolian sand transport, we used a large wind tunnel whose experimental section was 24.0 m‐long, 3.0 m‐wide and 2.0‐m high to provide enough length for aeolian transport and designed a set of novel experimental methods to improve the measurement accuracy of the aeolian transport rate. Based on experimental data, we developed a new equation for aeolian transport rate over bare and vegetated surfaces. We determined that models of aeolian transport rate over bare surface in the literature underestimated the aeolian transport rate measured in this study by 63–80%, 89%, 50% and 35%, confirming that the transport rate decreases exponentially as vegetation coverage increases. However, the power exponent is a variable related to particle size and wind velocity as opposed to a constant in the existing literature; thus, we proposed a dimensionless parameter to express the relationship between the power exponent with particle size and wind velocity and constructed the new equation for vegetated surfaces to be more widely applicable. These results would help to understand the effect of vegetation cover on aeolian sand transport process and to improve the effectiveness of vegetation prevention and control. Abstract : The results of a set of novel experiments confirmed that aeolian transport rate decreases exponentially as the vegetation coverage increases and the power exponent is a variable related to particle size and wind velocity. The relationship between the power exponent with particle size and wind velocity can be expressed by a dimensionless parameter ( u *t / u * ) 2 . These results help to develop a more widely applicable equation for aeolian transport rate over bare and vegetated surface.